Associations of the Neighborhood Built Environment with Gestational Weight Gain - Grobman, William A.; Crenshaw, Emma G.; Marsh, Derek J.; McNeil, Rebecca B.; Pemberton, Victoria L.; Haas, David M.; Debbink, Michelle; Mercer, Brian M.; Parry, Samuel; Reddy, Uma; Saade, George; Simhan, Hyagriv; Mukhtar, Farhana; Wing, Deborah A.; Kershaw, Kiarri N.; for the NICHD nuMoM2b NHLBI nuMoM2b Heart Health Study Networks (American Journal of Perinatology, 2021)
Objective This study aimed to determine whether specific factors of the built environment related to physical activity and diet are associated with inadequate and excessive gestational weight gain (GWG).Study Design This analysis is based on data from the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-To-Be, a prospective cohort of nulliparous women who were followed from the beginning of their pregnancies through delivery. At each study visit, home addresses were recorded and geocoded. Locations were linked to several built-environment characteristics such as the census tract National Walkability Score (the 2010 Walkability Index) and the number of gyms, parks, and grocery stores within a 3-km radius of residential address. The primary outcome of GWG (calculated as the difference between prepregnancy weight and weight at delivery) was categorized as inadequate, appropriate, or excessive based on weight gained per week of gestation. Multinomial regression (generalized logit) models evaluated the relationship between each factor in the built environment and excessive or inadequate GWG.Results Of the 8,182 women in the analytic sample, 5,819 (71.1%) had excessive GWG, 1,426 (17.4%) had appropriate GWG, and 937 (11.5%) had inadequate GWG. For the majority of variables examined, built environments more conducive to physical activity and healthful food availability were associated with a lower odds of excessive or inadequate GWG category. For example, a higher number of gyms or parks within 3 km of a participant's residential address was associated with lower odds of having excessive (gyms: adjusted odds ratio [aOR] = 0.93 [0.89–0.96], parks: 0.94 [0.90–0.98]) or inadequate GWG (gyms: 0.91 [0.86–0.96]; parks: 0.91 [0.86–0.97]). Similarly, a higher number of grocery stores was associated with lower odds of having excessive GWG (0.94 [0.91–0.97]).Conclusion Among a diverse population of nulliparous women, multiple aspects of the built environment are associated with excessive and inadequate GWG.Key Points
Keywords: neighborhood built environment; social determinants of health; gestational weight gain